Impact of Renal Function on Effectiveness and Safety Associated With Low Dose Dabigatran in Non-valve Atrial Fibrillation Patients After Catheter Ablation - Li, Xiaoye; Zuo, Chengchun; Ji, Qiuyi; Wang, Zi; Lv, Qianzhou (Frontiers in Cardiovascular Medicine, 2021)
AIM: The purpose of this study is to compare the effectiveness and safety of 110mg dabigatran in non-valve atrial fibrillation (NVAF) patients with different eGFRs. Methods: We conducted a single-center retrospective cohort study to investigate the effectiveness and safety of 110mg dabigatran for NVAF patients between January 2017 and December 2018 based on the eGFR category. Results: Results: A total of 560 NVAF patients who treated with 110mg dabigatran were included for analysis. In 12 months, the Kaplan-Meier survival curves indicated that the lower eGFR subgroups were more likely to experience thrombosis, bleeding, and cumulative events earlier (P=0.021 for thrombosis; P=0.026 for bleeding; P=0.001 for cumulative events). Gastrointestinal bleeding occurred more frequently in the moderate group than in other groups (6.94% in the moderate group vs 1.54% in the mild group vs 1.22% in the normal group, P=0.028). By multivariate analysis, chronic kidney disease (P=0.043; OR=4.273, 95%CI 1.043-17.543) and diabetes mellitus (P=0.023; OR=2.194, 95%CI 1.114-4.323) were independent predictors of the composite endpoints. A positive linear relationship was observed between eGFR levels and occurrence rate of thrombosis and bleeding under anticoagulation patients with 110mg dabigatran (R2=0.432 and R2=0.784, respectively). Conclusions: Impaired renal function was associated with decreased safety and increased thrombosis risks in NVAF patients taking low dose dabigatran.